Non-contextual teaching of sensitive topics focusing on cultural diversity in Polish schools = Bezkontekstowe nauczanie tematów drażliwych z uwzględnieniem różnorodności kulturowej w polskich szkołach - Markowska-Manista, Urszula (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to capture the specifics and validity of non-contextual teaching of sensitive topics focusing on the increasing cultural diversity in Polish schools. The term "non-contextual teaching" refers to teaching about cultural diversity in schools which were non-diverse for a long period of time, but are becoming increasingly culturally diverse. On the one hand, the paper looks at school asymmetries related to school curricula. On the other hand, it describes the needs of diverse groups of students and teachers connected with the decolonisation of educational content in the increasingly diversified world. Due to the limited space available in the paper, the article is only an attempt at signalling certain issues important for the subject at hand that can be a point of departure for further analysis and reflection about the necessity to decolonise school curricula.
Keywords: non-contextual teaching; sensitive topics; cultural diversity in Polish schools; decolonisation; nauczanie bezkontekstowe; tematy drażliwe; różnorodność kulturowa w polskich szkołach; dekolonizacja